PENGARUH PERTUNJUKAN ORGEN TUNGGAL TERHADAP MASYARAKAT DAN PEMUDA KAMPUNG AIR PANJANG JORONG KUAMANG KENAGARIAN PANTI TIMUR KECAMATAN PANTI KABUPATEN PASAMAN - Febri Iswanto; Tulus Handra Kadir; Yensharti Yensharti (SENDRATASIK UNP, 2018)
Abstract This Article aim to find and describe how orgen tunggal gave influence toward the society and youth of Kampung Air Panjang Jorong Kuamang Kenagarian Panti Timur Kabupaten Pasaman. Type of this study was qualitative with descriptive method. Technique of collecting data was done by using library research, investigation, interview, and documentation. Data was classified into two, they were primary and secondary. Based on result of the study, the show of orgen tunggal had influence which big enough toward the society and youth  of  Kampung Air Panjang Jorong Kuamang Kenagarian Panti Timur Kabupaten Pasaman. The influence it can be seen of positive perspective which was based on opinion that given by host were effective and low cost for the society and they were a practical entertainment and medium to show the singing talent. The influence of negative one which was based on society opinion, said that use rythm of the music were disturb, the sexy appearance of  the artists, appearance exceeded the time limit and the used of beer by the audiences in the show. Those things ruined image of orgen tunggal in Kampung Air Panjang Jorong Kuamang Kenagarian Panti Timur Kabupaten Pasaman. Keywords: positive influence, negative influence, orgen tunggal